The constitutionalization of nonhuman animals: analysis, reflections and proposals on the Chilean constitutional process - Henriquez Ramírez, Alfonso (Revista de Derecho Ambiental, 2023)
The recognition of animals within constitutional texts has aroused growing interest in recent years. Chile has not been the exception to this trend, which is also part of a process of profound legal changes, which have implied an improvement in protection standards. In this regard, we will seek to systematize some of the strategies that would allow the constitutionalization of animal law, highlighting their differences and assumptions. In this respect, we will distinguish between what we call the protection mandate, the rights approach, and the indirect or environmental approach. Subsequently, we will analyze how these strategies were incorporated during the first part of the Chilean constituent process, focusing on its scope and main problems. We will also highlight the role of civil society, and how it influenced the articles of the project. We will point out that the Convention tried to take elements from each of these strategies, but that this decision was not preceded by a longer-term discussion about the advantages or disadvantages of the different models. The lack of further reflection on this point explained the normative tensions that arose from the fact of trying to support approaches whose foundations were different or even contradictory. The study of this experience can be very useful for future constitutional amendment or change processes.